Development of a suite of short planetary health learning resources by students for students as future health professionals - Pais Rodrigues, Catarina; Papageorgiou, Evangelos; McLean, Michelle (Frontiers in Medicine, 2024)
Planetary health recognizes the interdependencies between human health and the well-being of the Earth's ecosystems. Human activities have led to the disruption and transformation of natural systems and a range of global environmental changes such as climate change, air pollution, and biodiversity loss. Health professionals must be equipped to deal with the health impacts of global environmental changes. This article describes the development and usage of a suite of 14 short online learning resources ('bricks') on Planetary Health on the ScholarRx platform. There are several principles that inform the development of these bricks, including learner-centric, peer learning, diversity, equity and inclusion, and authentic learning. The content is developed using a studenteducator collaboration model, supported by an editorial team. The suite of 14 modules was published in June 2023, with the initial usage data promising with 1,990 views in the first 10 months. These digital, modular resources allow for easy dissemination and can be incorporated in different programs depending on context and need.